Linking galaxy structural properties and star formation activity to black hole activity with IllustrisTNG - Habouzit, Mélanie; Genel, Shy; Somerville, Rachel S; Kocevski, Dale; Hirschmann, Michaela; Dekel, Avishai; Choi, Ena; Nelson, Dylan; Pillepich, Annalisa; Torrey, Paul; Hernquist, Lars; Vogelsberger, Mark; et al. (Monthly notices of the Royal Astronomical Society, 2019)
We study the connection between active galactic nuclei (AGN) and their host galaxies through cosmic time in the large-scale cosmological IllustrisTNG simulations. We first compare BH properties, i.e. the hard X-ray BH luminosity function, AGN galaxy occupation fraction, and distribution of Eddington ratios, to available observational constraints. The simulations produce a population of BHs in good agreement with observations, but we note an excess of faint AGN in hard X-ray ($L_{\rm x}\sim 10^{43-44}\, \rm erg/s$), and a lower number of bright AGN ($L_{\rm x}\gt 10^{44} \, \rm erg/s$), a conclusion that varies quantitatively but not qualitatively with BH luminosity estimation method. The lower Eddington ratios of the $10^{9}\, \rm M_{\odot }$ BHs compared to observations suggest that AGN feedback may be too efficient in this regime. We study galaxy star formation activity and structural properties, and design sample-dependent criteria to identify different galaxy types (star-forming/quiescent, extended/compact) that we apply both to the simulations and observations from the candels fields. We analyse how the simulated and observed galaxies populate the specific star formation rate - stellar mass surface density diagram. A large fraction of the $z$ = 0 $M_{\star }\geqslant 10^{11}\, \rm M_{\odot }$ quiescent galaxies first experienced a compaction phase (i.e. reduction of galaxy size) while still forming stars, and then a quenching event. We measure the dependence of AGN fraction on galaxies’ locations in this diagram. After correcting the simulations with a redshift and AGN luminosity-dependent model for AGN obscuration, we find good qualitative and quantitative agreement with observations. The AGN fraction is the highest among compact star-forming galaxies ($16-20{{\ \rm per\ cent}}$ at $z$ ∼ 1.5-2), and the lowest among compact quiescent galaxies ($6-10{{\ \rm per\ cent}}$ at $z$ ∼ 1.5-2).